2004
DOI: 10.1161/01.str.0000121646.23955.0f
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Ischemic Stroke in Relation to Age, Vascular Risk Factors, and Subtypes of Incident Stroke in Population-Based Studies

Abstract: Background-Appropriate design of molecular genetic studies of ischemic stroke requires an understanding of the genetic epidemiology of stroke. However, there are no published population-based data on heritability of aetiological subtypes of ischemic stroke, confounding by heritability of other vascular risk factors, or the relationship between heritability and age of onset. Methods-We studied family history of stroke (FHx Stroke

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
117
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 22 publications
10
117
1
Order By: Relevance
“…Only patients with CI younger than 70 years were recruited because previous studies revealed that genetic influence on CI is greater in younger patients 27,28) . Our aim was to investigate whether we could replicate this finding in a Chinese sample of relatively young individuals.…”
Section: Background Characteristicsmentioning
confidence: 99%
“…Only patients with CI younger than 70 years were recruited because previous studies revealed that genetic influence on CI is greater in younger patients 27,28) . Our aim was to investigate whether we could replicate this finding in a Chinese sample of relatively young individuals.…”
Section: Background Characteristicsmentioning
confidence: 99%
“…Evidence shows that genetic factors are more important in small-and large-vessel stroke than in cardio-embolic stroke [8,9] . Some intermediate phenotypes also exhibit high heritability, such as carotid intima-medial wall thickness (IMT) and white-matter lesions (WML) [3] .…”
Section: Ischemic Strokementioning
confidence: 99%
“…23 Family history of stroke is associated with proband hypertension in community-based and hospital-based populations with ischemic stroke. 24 In a pooled analysis of four populations with either stroke or TIA, family history of stroke was strongly related to history of hypertension in the proband, with an OR of 1.8 (95% CI, 1.3 to 2.5; p = 0.0008). 25 Several authors caution that hypertension may account for a significant component of the heritability of ischemic stroke.…”
Section: Discussionmentioning
confidence: 96%